»Ja, tam je en takšen, ko zna.« Vedeževalci – nasprotniki čarovnic na slovenskem podeželju »Yeah, There’s Someone Who ‘Knows’.« Soothsayers as Counterwitches in Rural Slovenia - Mencej, Mirjam (Studia mythologica Slavica, 2006)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The article focuses on the soothsayers who functioned as counterwitches, and were consulted in the case of witch assault. Analyzed are the reasons why people enlisted the help of a soothsayer; their location; their sex structure; techniques and implements they had used; procedure phases required to nullify the evil curse (confirmation of witch assault, identification of the witch, nullification of the curse, and eventual reversing of the curse and revenge upon the witch); their payment; and people’s attitude toward them.